Product Profile and Marketing Channels used by Milk Processors in Karnal District of Haryana (Indian Journal of Extension Education, 2017)
India is the largest milk producing country in the world; milk production is more than 127 million tons in a year. Out of the entire production, 55 per cent are consumed as fluid milk and rest 45 per cent are sent for industrial processing. In spite of having largest milk production, India is a very minor player in the world market. Hence, there is a crucial need to develop entrepreneurship in the field of milk processing. For the present study. Karnal district of Haryana was selected purposively for its importance in milk production and processing due to presence of NDRI. The objective was to find out the product profile and marketing channels used by dairy entrepreneurs. There were 41 registered milk processors and all the processors were interviewed for the study as respondents. It was observed that all the respondents process their available milk for butter, ghee, paneer and dahi. In addition with these major products, the respondents were also manufacturing ice-cream, khoa, cheese, lassi, flavoured milk, etc. Paneer, butter, ghee and dahi were the major dairy products preferred and consumed by the people in the study area.